A tecnologia lítica dos antigos grupos humanos de Carajás: sítio Capela (PA-AT-337: S11D 47/48) - Renata Rodrigues Maia (2017)
The present research has the proposal to study the lithic vestiges coming from an archaeological site located in the Amazon, more precisely in the region of Carajás, southeast of Pará, based on the concepts of Technological Analysis and Operational Chain developed by the French School (Mauss, 1974; Leroi-Gourhan, 1972, 1983; Inizian et al., 1995; Tixier, 1980; Pelegrin, 2004, 2009, 2015, among others). The objective is to analyze the lithic industries of the site PA-AT-337: S11D 47/48 (Capela) with the purpose of interpreting the distribution and the spatial / temporal organization of the industries, following the concepts of the morphotechnological studies. With this we intend to see the possible chronological changes and cultural preferences through comparisons between stratigraphic levels. In addition, this research intends to discuss the context to which the archaeological site is located, highlighting the study of the landscape, together with the results of the analyzes of the other archaeological remains found in the site.